Anais Brasileiros de Dermatologia: 100 years of history (1925‒2025) - Marques, Silvio Alencar; Roselino, Ana Maria Ferreira; de Almeida, Hiram Larangeira; Abbade, Luciana Patricia Fernandes (Elsevier, 2024)
The month of January 1925 marks the birth of the Annaes Brasileiros de Dermatologia e Syphilografia and currently, 100 years later, with great merit, we celebrate its evolution into Anais Brasileiros de Dermatologia (ABD). Indeed, those few brilliant pioneers never dreamed of the strength of the Brazilian Society of Dermatology nowadays. However, perhaps they envisioned a relevant role for ABD, with a natural space for dermatoses of infectious etiology, always prevalent in tropical and subtropical regions. And thus, it was established for decades. Currently, Brazilian Dermatology and ABD are plural and open to the different facets of Dermatology. However, both the specialty, Dermatology, and its official body, ABD, value and pay homage to history, and cannot forget or stray from it. Numerous challenges have been faced over the past 100 years. Many other challenges still remain, but it is up to us, as a gift to the 100th anniversary of the Anais Brasileiros de Dermatologia, to learn about them and reflect on them. The following text provides a summary of the history of ABD over the years. We invite national and international readers to celebrate with us.